ANALISIS EFEKTIVITAS PEMBIAYAAN KUR SYARIAH DALAM PENGEMBANGAN USAHA BUDIDAYA KEPITING ( Studi Pada Usaha Budidaya Kepiting Desa Pallae, Kec.Cenrana) - Jumerlia; keri, Ismail; Muh.Hasbi Ash.Shiddiq (LP2M IBK Nitro, 2025)
This study aims to analyze the effectiveness of KUR Syariah financing in developing crab farming businesses in Pallae Village, Cenrana District, and to review the strategies of Islamic Banks in increasing the effectiveness of such financing. This issue is important considering the potential of the crab farming sector in driving the economy of coastal communities. This study uses a qualitative approach with interview techniques, and documentation of crab farming business actors. Data were analyzed through a process of reduction, presentation, and drawing conclusions descriptively. The results of the study indicate that KUR Syariah financing is effective in increasing the scale of business, income, and welfare of farmers. The bank's strategy in the form of periodic assistance and coaching also supports the success of this program. KUR Syariah has proven to be a financing solution that is in accordance with sharia principles and has a positive impact on the development of productive businesses.